Numerical modeling of influence parameters in cavabililty of rock mass in block caving mines. (May 2018) - Rafiee, R.; Ataei, M.; KhalooKakaie, R.; Jalali, S.E.; Sereshki, F.; Noroozi, M.
Abstract: The prediction of rock mass cavability is needed in the design of block caves to estimate the undercut size required to achieve continuous caving. The cavability of the rock mass will control mine design and economic issues for a given geological environment and is a fundamental issue in establishing a successful block caving mine. With recent interest in applying caving techniques to stronger rock masses, the reliable prediction of rock mass cavability is becoming increasingly important. The two most universally applied methods for cavability prediction are the empirical stability graph approach developed by Laubscher and numerical methods. Empirical approaches developed to predict rock mass cavability have been based on the assessment of rock mass conditions using recognized rock mass classification schemes. Rock mass classification is the first stage in empirical approaches to predicting rock mass cavability. The numerical approaches also commonly utilize rock mass classification schemes to assign rock mass properties and apply failure criteria within the models. A reliable prediction of cavability of rock mass depends on the accurate identification of the influence parameters in rock mass cavability. The cavability of a rock mass is based on many factors such as natural and induced factors, affect the caving performance. In this paper the effect of seven parameters, the compressive strength of intact rock (UCS), joint orientation, joint persistence, joint density (P32 ), joint friction, confined stress and hydraulic radius (HR), is investigated using numerical technique named the Synthetic Rock Mass (SRM). The SRM is a numerical modeling technique which combines the Bonded Particle Model (PFC) for intact rock and Discrete Fracture Network (DFN) simulation. To assess the influence of each parameter in numerical modeling, the value of one parameter is changing while the values of other six parameters are fixed. It is found that in-situ stress and hydraulic radius are the most effective parameters in cavability of rock mass in block caving mines.